Dimerization partners determine the activity of the Twist bHLH protein during Drosophila mesoderm development. - Castanon, I.; Von Stetina, S.; Kass, J.; Baylies, M.K. (Development, 2001)
The basic helix-loop-helix transcription factor Twist regulates a series of distinct cell fate decisions within the Drosophila mesodermal lineage. These twist functions are reflected in its dynamic pattern of expression, which is characterized by initial uniform expression during mesoderm induction, followed by modulated expression at high and low levels in each mesodermal segment, and finally restricted expression in adult muscle progenitors. We show two distinct partner-dependent functions for Twist that are crucial for cell fate choice. We find that Twist can form homodimers and heterodimers with the Drosophila E protein homologue, Daughterless, in vitro. Using tethered dimers to assess directly the function of these two particular dimers in vivo, we show that Twist homodimers specify mesoderm and the subsequent allocation of mesodermal cells to the somatic muscle fate. Misexpression of Twist-tethered homodimers in the ectoderm or mesoderm leads to ectopic somatic muscle formation overriding other developmental cell fates. In addition, expression of tethered Twist homodimers in embryos null for twist can rescue mesoderm induction as well as somatic muscle development. Loss of function analyses, misexpression and dosage experiments, and biochemical studies indicate that heterodimers of Twist and Daughterless repress genes required for somatic myogenesis. We propose that these two opposing roles explain how modulated Twist levels promote the allocation of cells to the somatic muscle fate during the subdivision of the mesoderm. Moreover, this work provides a paradigm for understanding how the same protein controls a sequence of events within a single lineage.